IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) ROYAL GOLDEN EAGLE (RGE) GROUP DI TIONGKOK TAHUN 2013-2018 (STUDI KASUS ASIA SYMBOL) - Chandra Abet Nego Siagian; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This is an analysis of study of international political economy. It discusses the implementation of foreign direct investment by the RGE group in China through its business unit Asia Symbol Shandong and Asia Symbol Guangdong. RGE group is an MNC (Multinational Corporation) which was established in Indonesia in 1973 and started investment activities in China in 2002. This study aims to determine the implementation of the RGE group CSR (Corporate Social Responsibility) program in China through ASIA SYMBOL in the 2013 period -2018.                This research uses neoliberalism prespective, and its supported by Corporate Social Responsibility theory. This research applies qualitative method with descriptive analysis. Data collection techniques in this research are media interviews and literature study.                              This research show the implementation of the RGE CSR group in China through Asia Symbol companies in the form of company contributions to every part of the life of the local community. CSR programs that are implemented include the social, economic and environmental. Keywords: CSR, Implementation, RGE, MNC, Tiongkok